2016
DOI: 10.1002/jcsm.12144
|View full text |Cite
|
Sign up to set email alerts
|

Lipid modulation of skeletal muscle mass and function

Abstract: Loss of skeletal muscle mass is a characteristic feature of various pathologies including cancer, diabetes, and obesity, as well as being a general feature of ageing. However, the processes underlying its pathogenesis are not fully understood and may involve multiple factors. Importantly, there is growing evidence which supports a role for fatty acids and their derived lipid intermediates in the regulation of skeletal muscle mass and function. In this review, we discuss evidence pertaining to those pathways wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
166
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 117 publications
(246 reference statements)
8
166
0
5
Order By: Relevance
“…Accumulation of intramuscular lipids plays a pathogenic role in insulin resistance and type 2 diabetes . Finally, several recent studies highlighted the involvement of fatty acids and their metabolites, such as DAG and ceramides, in blocking muscle growth and altering myofiber metabolism . For this reason, we investigated how the modulation of Plin2 expression could affect the lipid metabolites in adult skeletal muscle and whether this can account for the observed effect on myofiber size.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Accumulation of intramuscular lipids plays a pathogenic role in insulin resistance and type 2 diabetes . Finally, several recent studies highlighted the involvement of fatty acids and their metabolites, such as DAG and ceramides, in blocking muscle growth and altering myofiber metabolism . For this reason, we investigated how the modulation of Plin2 expression could affect the lipid metabolites in adult skeletal muscle and whether this can account for the observed effect on myofiber size.…”
Section: Discussionmentioning
confidence: 95%
“…Skeletal muscle is another important player in lipid metabolism. In fact, intracellular accumulation of fatty acids has been reported to affect both muscle mass and function . The role of Plin2 in muscle physiopathology has not been yet dissected.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms mediating metabolic lipotoxicity are complex and appear to include direct pro-oxidative and inflammatory activities [28] as well as accumulation of metabolically toxic lipid moieties such as diacylglycerol and ceramides [34]. Recent evidences show that ectopic lipid deposition may also compromise muscle protein turnover [35].…”
Section: Introduction: What We Knowmentioning
confidence: 99%
“…Sarcopenia can also be diagnosed by measuring the psoas muscle area (4,5). Although nutritional management of cancer patients to prevent and resolve sarcopenia has not been established, attention has been focused on the effects of fatty acid administration on cancer patients (6)(7)(8). Furthermore, studies that have identified a relationship between a significant decrease in psoas muscle volume and CRP increase in patients with cancer cachexia (9).…”
mentioning
confidence: 99%